The Sasak Tribe of Intercultural Communication in Lombok, West Nusa Tenggara - Yuni Permata (IAHN-TP Palangka Raya, 2024)
This paper explores the intercultural communication dynamics of the Sasak tribe, indigenous to Lombok, Indonesia. With globalization affecting cultural interactions, understanding the communication methods within and involving the Sasak people is increasingly crucial. The study uses a qualitative approach to gather data on the Sasak tribe's rich cultural heritage, which is influenced by indigenous traditions and marked by distinct language, arts, customs, and social structures.Key intercultural communication theories are applied to analyze the Sasak tribe’s interactions. Hofstede’s Cultural Dimensions Theory reveals the tribe's tendencies towards high power distance, strong collectivism, moderate to high uncertainty avoidance, and long-term orientation. Howard Giles’ Communication Accommodation Theory explains how the Sasak people adjust their communication styles through convergence and divergence when interacting with different cultural groups. Stella Ting-Toomey’s Face Negotiation Theory provides insights into the importance of face-saving and face-giving strategies in maintaining respect and honor in Sasak culture. William Gudykunst’s Anxiety/Uncertainty Management Theory highlights the role of mindfulness and cultural empathy in effective intercultural communication. The study concludes that these theories provide valuable frameworks for understanding the Sasak tribe's cultural interactions, emphasizing the need for mutual respect and understanding in an interconnected world. By integrating these theories, we gain a comprehensive appreciation of the complexities in the Sasak tribe’s communication practices, promoting effective and respectful intercultural interactions.